PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA DI SMPN 13 PADANG - Lidia Putri Anggraini (Departemen Matematika, 2018)
The mathematical communication skills is one of the capabilities that must be possessed by each learners. This study aims to determine the effect of mathematical communication skills learning using think talk write type learning model with conventional learning. This type of research is a pseudo experiment with the design of research static group design. Data on the mathematical communication skills of learners were taken through the result of communication skills tests and analyzed by using U Mann Whitney test. The result showed that the mathematical communication skills of learners using the TTW type learning model is better than the conventional learning mathematical communication skills of learners using the conventional learning. Keywords — mathematical communication skills, Think Talk Write, conventional learning.